Cohesin: a catenase with separate entry and exit gates? - Nasmyth, K (2011)
Cohesin confers both intrachromatid and interchromatid cohesion through formation of a tripartite ring within which DNA is thought to be entrapped. Here, I discuss what is known about the four stages of the cohesin ring cycle using the ring model as an intellectual framework. I postulate that cohesin loading onto chromosomes, catalysed by a separate complex called kollerin, is mediated by the entry of DNA into cohesin rings, whereas dissociation, catalysed by Wapl and several other cohesin subunits (an activity that will be called releasin here), is mediated by the subsequent exit of DNA. I suggest that the ring's entry and exit gates may be separate, with the former and latter taking place at Smc1-Smc3 and Smc3-kleisin interfaces, respectively. Establishment of cohesion during S phase involves neutralization of releasin through acetylation of Smc3 at a site close to the putative exit gate of DNA, which locks rings shut until opened irreversibly by kleisin cleavage through the action of separase, an event that triggers the metaphase to anaphase transition.